Relasi Etnisitas dan Industrialisasi Era Kolonial Inggris di Malaysia - zulhair, muhaimin (Jurusan Hubungan Internasional UNHAS, 2015)
Ethnicity and industrialization are usually analyzed separately. Even if seen interlink, the analysis will focus on the industrial production process itself (actor proximity, component makers, and industry sustainability). This paper is about to come out of the tradition as it is to be linked with the historical colonial practice that will give to a more comprehensive understanding. By taking the Malaysia colonial context is expected to show the linkages. The issue of ethnicity in this paper is not seen as something that stands alone and domestic but is related to the practice of the colonial political economy strategy to manage the problems become the dominant discourse.